Structural and Electrophysiological Changes in a Model of Cardiotoxicity Induced by Anthracycline Combined With Trastuzumab - Altomare, Claudia; Lodrini, Alessandra Maria; Milano, Giuseppina; Biemmi, Vanessa; Lazzarini, Edoardo; Bolis, Sara; Pernigoni, Nicolò; Torre, Eleonora; Arici, Martina; Ferrandi, Mara; Barile, Lucio; Rocchetti, Marcella; et al. (Frontiers in Physiology, 2021)
Background Combined treatment with anthracyclines (e.g., doxorubicin; Dox) and trastuzumab (Trz), a humanized anti-human epidermal growth factor receptor 2 (HER2; ErbB2) antibody, in patients with HER2-positive cancer is limited by cardiotoxicity, as manifested by contractile dysfunction and arrhythmia. The respective roles of the two agents in the cardiotoxicity of the combined therapy are incompletely understood. Objective To assess cardiac performance, T-tubule organization, electrophysiological changes and intracellular Ca2+ handling in cardiac myocytes (CMs) using an in vivo rat model of Dox/Trz-related cardiotoxicity. Methods and Results Adult rats received 6 doses of either Dox or Trz, or the two agents sequentially. Dox-mediated left ventricular (LV) dysfunction was aggravated by Trz administration. Dox treatment, but not Trz, induced T-tubule disarray. Moreover, Dox, but not Trz monotherapy, induced prolonged action potential duration (APD), increased incidence of delayed afterdepolarizations (DADs) and beat-to-beat variability of repolarization (BVR), and slower Ca2+ transient decay. Although APD, DADs, BVR and Ca2+ transient decay recovered over time after the cessation of Dox treatment, subsequent Trz administration exacerbated these abnormalities. Trz, but not Dox, reduced Ca2+ transient amplitude and SR Ca2+ content, although only Dox treatment was associated with SERCA downregulation. Finally, Dox treatment increased Ca2+ spark frequency, resting Ca2+ waves, sarcoplasmic reticulum (SR) Ca2+ leak, and long-lasting Ca2+ release events (so-called Ca2+ “embers”), partially reproduced by Trz treatment. Conclusion These results suggest that in vivo Dox but not Trz administration causes T-tubule disarray and pronounced changes in electrical activity of CMs. While adaptive changes may account for normal AP shape and reduced DADs late after Dox administration, subsequent Trz administration interferes with such adaptive changes. Intracellular Ca2+ handling was differently affected by Dox and Trz treatment, leading to SR instability in both cases. These findings illustrate the specific roles of Dox and Trz, and their interactions in cardiotoxicity and arrhythmogenicity.